ADOLESCENT INTERACTION IN COMMUNITY CULTURE AND LANGUAGE 5:0 - Dieni, Asmira; Sari, Siti Mayang (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Descriptive qualitative research with the case study method is a research approach used to gain an in-depth understanding of a particular phenomenon, event, or case in a real context. Researchers observe phenomena in their natural environment without manipulation. The research seeks to understand the perspectives and experiences of participants. Data are collected through interviews, observations, documents, or artifacts. Researchers describe the data in depth, providing an overview of emerging themes or patterns, such as: How adolescents in a particular community practice local languages ​​in everyday conversation. The role of local culture in shaping adolescents' social identities at school. The influence of peer groups on the use of slang in social media.Today's teenagers often use sentences in language and culture that resemble foreign languages ​​or are called